1997
DOI: 10.1182/blood.v89.3.801
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Therapy and Autologous Hematopoietic Progenitor Cell Transplantation for Recurrent or Refractory Hodgkin's Disease: Analysis of the Stanford University Results and Prognostic Indices

Abstract: One hundred nineteen patients with relapsed or refractory Hodgkin's disease (HD) received high-dose therapy followed by autologous hematopoietic progenitor cell transplantation. Three preparatory regimens, selected on the basis of prior therapy and pulmonary status, were employed. Twenty-six patients without a history of prior chest or pelvic irradiation were treated with fractionated total body irradiation, etoposide (VP) 60 mg/kg and cyclophosphamide (Cy) 100 mg/kg. Seventy-four patients received BCNU 15 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
77
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(91 citation statements)
references
References 39 publications
11
77
1
2
Order By: Relevance
“…For the past two decades, we have incorporated accelerated fractionation radiotherapy (RT) either as total lymphoid irradiation (TLI) or as an involved field (IF-RT) into our transplant conditioning regimen. In an initial study conducted from 1986 to 1993, at Memorial Sloan-Kettering Cancer Center (MSKCC), chemosensitive disease was not required in order to be eligible for ASCT, and despite this, the 10-year survival following ASCT was 45%, with no relapses occurring >3 years following HDT (Moskowitz et al, 2001;Horning et al, 1997). Like others, we found a marked survival advantage for patients with chemosensitive disease, and required evidence of chemosensitivity in our subsequent protocols (Josting et al, 2002).…”
supporting
confidence: 58%
“…For the past two decades, we have incorporated accelerated fractionation radiotherapy (RT) either as total lymphoid irradiation (TLI) or as an involved field (IF-RT) into our transplant conditioning regimen. In an initial study conducted from 1986 to 1993, at Memorial Sloan-Kettering Cancer Center (MSKCC), chemosensitive disease was not required in order to be eligible for ASCT, and despite this, the 10-year survival following ASCT was 45%, with no relapses occurring >3 years following HDT (Moskowitz et al, 2001;Horning et al, 1997). Like others, we found a marked survival advantage for patients with chemosensitive disease, and required evidence of chemosensitivity in our subsequent protocols (Josting et al, 2002).…”
supporting
confidence: 58%
“…Namely, the quality of response to salvage chemotherapy remains one of the strongest predictors for long-term survival in patients with relapsed/refractory HL undergoing ASCT. Several studies showed that chemoresistance or suboptimal response to pretransplant salvage chemotherapy represents the major adverse prognostic factors affecting PFS [5,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Disease recurrence is the main cause of ASCT failure. Duration of response to upfront treatment, poor sensitivity to pre-transplant salvage chemotherapy and early disease progression after ASCT were shown to be the most important predictors of unfavourable outcome in HL patients undergoing ASCT (Crump et al, 1993;Horning et al, 1997;Lazarus et al, 2001;Moskowitz et al, 2001;Josting et al, 2002Josting et al, , 2005Sureda et al, 2005;Majhail et al, 2006;Smith et al, 2011;Mart ınez et al, 2013;Hertzberg, 2014). Accordingly, the persistence of metabolically active lymphoma lesions after salvage therapy and/or conditioning, as evidenced by 18F fluorodeoxyglucose positron emission tomography ( 18F FDG-PET), emerged as the strongest independent predictor for PFS and overall survival (OS) in patients with relapsed and refractory (RR) HL treated with ASCT (Hutchings, 2011;Smeltzer et al, 2011;Devillier et al, 2012;Moskowitz et al, 2012;von Tresckow & Engert, 2012;Akhtar et al, 2013;Hertzberg, 2014;Pinto et al, 2014).…”
mentioning
confidence: 99%